To be is to be perceived, not to be is not to be perceived - Guillaume Le Blanc (Presses Universitaires de la Méditerranée, 2021)
Can we say that to be is to be perceived? Or that not to be is not to be perceived? Who decides who is to be visible or not? My contention is that invisibility is a social construction related to norms of apprehension, recognition and justification. Not seeing a person makes them absent, and precipitates them into social death. What happens when one is thus made invisible? Can one’s voice bring one back to life? And under what conditions is a silent voice still a living voice? Why is invisibility always attached to inaudibility? If losing one’s voice means losing one’s face, then keeping one’s voice, even when it is lost, allows an inner face to appear, a face that escapes from the eyes of others and is yet present. What is the future of this face?